EKSPLORASI PRAKTIK AKUNTANSI BERBASIS TEKNOLOGI INFORMASI DI KELURAHAN PLERET BANTUL YOGYAKARTA - DEVI KUSUMAWARDHANI - (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2023)
Abstract This study aims to explore the information technology-based accounting practices in Pleret Village, Bantul, using an ethnomethodological approach. The research investigates the implementation of information technology, its benefits, and the challenges faced in the accounting practices of the village. The study's theoretical framework incorporates theories of social interaction and accounting practices, meaning negotiation and the use of information technology, social construction and the reality of accounting, as well as local context and accounting practices. The research employed a qualitative research design, utilizing interviews, observations, and document analysis as data collection methods. The informants included employees from the local government office, accountants or financial consultants, system users, and community stakeholders. Through an in-depth analysis of the data, the study reveals several findings. The findings of this study contribute to both empirical and theoretical knowledge. Empirically, the research provides insights into the specific context of information technology-based accounting practices in Pleret Village. Theoretical implications include a deeper understanding of the role of social interaction in shaping accounting practices, the negotiation of meaning in the adoption and use of information technology, the social construction of accounting reality, and the influence of local context on accounting practices.